Pengembangan Perangkat Pembelajaran Sistem Operasi Berbasis Project Based Learning Untuk Sekolah Menengah Kejuruan - Charis Fathul Hadi; Bambang Suprianto; Agus Budi Santosa (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
Curriculum 2013 is a student-centered learning, where one of them is learning project based learning that is suitable for scientific study. SMK, it is not yet available any project-based learning tool. Therefore, this study aims to produce project-based learning project which is feasible and can be used to support the implementation of the curriculum 2013 on the subjects of Operating Systems Multimedia at Class X in SMK This study uses a 4D model (define, design, develop, and disseminate), where the theoretical feasibility obtained through validation by experts. The data were analyzed in descriptive quantitative. Results of the assessment showed that the learning tools is feasible and can be used in learning at SMK. The theoretical feasibility of the learning tools is described as follows : (1) the syllabus of 88.25% (2) 87.5% RPP (3) Books 83.5% (4) LKS 86.75% (5) 87.5% Products LP (6) LP psychomotor 86.25% (7) items 86% (8) 89.25% student response, learning feasibility of 81.36%, as well as the achievement of competence indicator of good attitude reached 100%, while the competence indicator of knowledgemastery and skills of each student reached 100%, while the response of students reached 86.87%